ANALISIS PERUBAHAN PENGGUNAAN LAHAN DISEPANJANG JALAN BARU AROSUKA UNTUK PEMANFAATAN RUANG KABUPATEN SOLOK - Putri Wulandari; Erna Juita; Elvi Zuriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze changes in land use along Jalan Baru Arosuka and their implications for spatial utilization in Solok Regency. The development of Jalan Baru Arosuka has improved accessibility and connectivity between regions, thereby encouraging the conversion of land from agriculture to residential, commercial, and public facilities. The research method used is mixed methods, combining spatial analysis using Geographic Information Systems (GIS) with a qualitative approach through in-depth interviews. Research data were obtained from Landsat and Sentinel satellite imagery for 2015, 2020, and 2024, as well as field surveys and questionnaires distributed to 98 heads of households on Jalan Baru Arosuka, Solok Regency. The research results show a decrease in the area of rice fields from 588.2 hectares in 2015 to 268.74 hectares in 2024, while the residential area increased from 37.6 hectares in 2015 to 85.10 hectares in 2024. The most significant changes occurred within a radius of 0–500 meters from the road, with the direction of residential and economic activity development following an east–west corridor. These land use changes impact increased economic activity, changes in the social structure of the community, and a potential decline in food security due to the reduction of productive land. These findings underscore the importance of spatial planning integrated with infrastructure development to achieve sustainable land use in Solok Regency.